NP-59 Adrenal Scintigraphy as an Imaging Biomarker to Predict KCNJ5 Mutation in Primary Aldosteronism Patients - Lu, Ching-Chu; Yen, Ruoh-Fang; Peng, Kang-Yung; Huang, Jei-Yie; Wu, Kwan-Dun; Chueh, Jeff S.; Lin, Wan-Yu (Frontiers in Endocrinology, 2021)
Purpose: Somatic KCNJ5 mutation occurs in half of unilateral primary aldosteronism (PA) and is associated with more severe phenotype. Mutation status can only be identified by tissue sample from adrenalectomy. NP-59 adrenal scintigraphy is a noninvasive functional study for disease activity accessment. This study aimed to evaluate the predictive value of NP-59 adrenal scintigraphy in somatic KCNJ5 mutation among PA patients who received adrenalectomy. Methods: Sixty-two PA patients who had NP-59 adrenal scintigraphy before adrenalectomy with available KCNJ5 mutation status were included. Two semiquantitative parameters, adrenal to liver ratio (ALR) and lesion to contralateral ratio of bilateral adrenal glands (CON) derived from NP-59 adrenal scintigraphy, of mutated and wild-type patients were compared. Cutoff values calculated by receiver-operating characteristic (ROC) analysis were used as a predictor of KCNJ5 mutation. Results: Twenty patients had KCNJ5 mutation and 42 patients were wild type. Patients harboring KCNJ5 mutation had both higher ALR and CON (p=0.0031 and 0.0833, respectively) than wild-type patients. With ALR and CON cutoff of 2.10 and 1.95, the sensitivity and specificity to predict KCNJ5 mutation were 85%, 57% and 45%, 93%, respectively. Among 20 patients with KCNJ5 mutation, 16 showed G151R point mutation (KCNJ5- G151R) and 4 showed L168R point mutation (KCNJ5-L168R), which former one had significantly lower ALR (p=0.0471). Conclusion: PA patients harboring somatic KCNJ5 mutation had significantly higher NP-59 uptake regarding to ALR and CON than those without mutation. APAs with KCNJ5-L168R point mutation showed significantly higher ALR than those with KCNJ5-G151R point mutation.